2016
DOI: 10.1093/annhyg/mew022
|View full text |Cite
|
Sign up to set email alerts
|

A Method for Semi-quantitative Assessment of Exposure to Pesticides of Applicators and Re-entry Workers: An Application in Three Farming Systems in Ethiopia

Abstract: This study indicated that farmers' and farm workers' exposure to pesticides can be inexpensively characterized, ranked, and classified. Our method could be extended to assess exposure to specific active ingredients provided that detailed information on pesticides used is available. The resulting exposure estimates will consequently be used in occupational epidemiology studies in Ethiopia and other similar countries with few resources.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 22 publications
0
32
1
Order By: Relevance
“…A study in LSGHs in Ethiopia reported a similar high risk for respiratory symptoms among cutters and weeders when compared with other unexposed farm workers (packing and bundling) (ie, OR of 2.2 (95% CI 1.0 to 5.1) and 1.8 (95% CI 0.9 to 3.8)) for chronic cough and shortness of breath, respectively 1. These risks are lower than the risks observed in our study which possibly can be explained by the fact that the reference workers in packing and bundling might still have the potential for pesticide exposure as indicated by our previously developed exposure algorithm for re-entry workers23 and the fact that among these workers’ elevated risks for respiratory symptoms were observed in our study.…”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…A study in LSGHs in Ethiopia reported a similar high risk for respiratory symptoms among cutters and weeders when compared with other unexposed farm workers (packing and bundling) (ie, OR of 2.2 (95% CI 1.0 to 5.1) and 1.8 (95% CI 0.9 to 3.8)) for chronic cough and shortness of breath, respectively 1. These risks are lower than the risks observed in our study which possibly can be explained by the fact that the reference workers in packing and bundling might still have the potential for pesticide exposure as indicated by our previously developed exposure algorithm for re-entry workers23 and the fact that among these workers’ elevated risks for respiratory symptoms were observed in our study.…”
Section: Discussioncontrasting
confidence: 61%
“…Pesticide exposure was assessed both qualitatively and semiquantitatively as previously described in Negatu et al 23. The exposures assessment was based on exposure estimates obtained from exposure algorithms developed separately for applicators and re-entry workers.…”
Section: Methodsmentioning
confidence: 99%
“…*Khat is an evergreen shrub of eastern Africa and Arabia; its leaves have narcotic properties.†Exposure units, estimates of occupational pesticide exposure using algorithms as described in Negatu et al 27.…”
Section: Resultsmentioning
confidence: 99%
“…†Exposure units, estimates of occupational pesticide exposure using algorithms as described in Negatu et al 27.…”
Section: Resultsmentioning
confidence: 99%
“…Negatu et al (49) developed two semi-quantitative exposure algorithms to assess cumulative exposure to pesticides in a group of applicators and re-entry workers of different farming systems in Ethiopia. These algorithms were based on detailed exposure factors, including application methods, farm layout (open or closed), pesticide mixing circumstances, the cleaning of spraying equipment, the amount of pesticide application per day, the utilization of PPE, personal hygienic behavior, the annual frequency of application, and the length of employment at the farm.…”
Section: Use Of Job-exposure Matrices and Quantitative Algorithmsmentioning
confidence: 99%